Peningkatan Kemandirian Ekonomi pada Pembentukan Koperasi Merah Putih di Desa Kalisari Kecamatan Banyuglugur Kabupaten Situbondo - Afton Ilman Huda; Multazem; Moh. Faqih; Hairul Diofani; Abdullah Maulana Azzaky; Muhammad Jaiz (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study explores the efforts to enhance economic independence through the establishment of the Koperasi Merah Putih (Red and White Cooperative) in Kalisari Village, Banyuglugur District, Situbondo Regency. The cooperative serves as a strategic initiative to empower the local community, particularly small-scale farmers and micro-entrepreneurs, by promoting collective economic activities based on mutual cooperation and local potential. Using a qualitative descriptive method, this research highlights the formation process, challenges, and early impacts of the cooperative. Findings indicate that the cooperative plays a significant role in fostering economic resilience, increasing community participation, and improving access to financial and business resources. However, sustainability still depends on continuous guidance, strong leadership, and consistent member involvement. This study suggests that with proper management and government support, community-based cooperatives like Koperasi Merah Putih can be a vital instrument in building rural economic independence.